2009
DOI: 10.1017/s1041610208008399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of end of life with dementia by families in Dutch and U.S. nursing homes

Abstract: Background:The End-of-Life in Dementia (EOLD) scales comprise the most specific set of instruments developed for evaluations of patients' end of life by their families. It is not known whether the EOLD scales are useful for cross-national comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
0
25
3
Order By: Relevance
“…One paper reports survey data that used End of Life in Dementia Scales, but this review only includes findings from the 'Satisfaction with Care Tool' used to elicit family perspectives within the study. 48 Three of the studies were longitudinal, two of which collected qualitative data. One study used a concurrent mixed methods design 49 and one used a prospective cohort study design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One paper reports survey data that used End of Life in Dementia Scales, but this review only includes findings from the 'Satisfaction with Care Tool' used to elicit family perspectives within the study. 48 Three of the studies were longitudinal, two of which collected qualitative data. One study used a concurrent mixed methods design 49 and one used a prospective cohort study design.…”
Section: Resultsmentioning
confidence: 99%
“…Family carers frequently rated an item on information and decision-making as not applicable in a study from the Netherlands where a model of shared decision-making is in place. 48 Family carers' responses indicated that they were well informed regarding the condition of their relative and that decisions were shared between family carers and professionals. This shared decision-making model is characterized by family involvement from the moment of admission of the person to the nursing home and open ongoing dialogue between family members and professionals.…”
Section: Making Decisionsmentioning
confidence: 99%
“…In addition to pain and shortness of breath, US and Dutch families and Dutch nurses also reported that dementia patients experienced discomfort, restlessness, and difficulty swallowing more than other symptoms [53,54]. Agitation is a symptom which is less frequently assessed in studies on the last phase of life, but may be as common as pain and shortness of breath [28,34,44,53,54].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
“…Agitation is a symptom which is less frequently assessed in studies on the last phase of life, but may be as common as pain and shortness of breath [28,34,44,53,54]. One study found that psychiatric symptoms such as agitation and depression were less bothersome to family members than pain, breathing problems, and memory loss [46].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
See 1 more Smart Citation